(untitled) (World Bulletin of Social Sciences, 2023)
The article covers such concepts as sales service, sales service quality, and sales culture. It analyzed the indicators of the quality of sales service provided to customers at the "Korzinka.uz" supermarket in cities and made recommendations for their improvement.